Mind the Gap : Disparities in Assessments of Living Standards Using National Accounts and Household Surveys - Prydz, Espen Beer; Jolliffe, Dean; Serajuddin, Umar (World Bank, Washington, DC, 2021)
Estimates of average per capita consumption and income from national accounts differ substantially from corresponding measures of consumption and income from household surveys. Using a new compilation of more than 2,000 household surveys matched to national accounts data, this study finds that the gaps between the data sources are larger and more robust than previously established. Means of household consumption estimated from surveys are, on average, 20 percent lower than corresponding means from national accounts. The gap with gross domestic product per capita is nearly 50 percent. The gaps have increased in recent decades and are largest in middle-income countries, where annualized growth rates for consumption surveys are systematically lower than national accounts growth rates. The paper shows that the gaps in measures across these two sources have implications for assessments of economic growth, poverty, and inequality. The study finds that typical survey measures of consumption and income may exaggerate poverty reduction and underestimate inequality.